Automatic feature description of Endometrioma in Ultrasonic images of the ovary - Mus’ab Sahrim; Wan Zakiah Wan Ismail; Juliza Jamaludin; Sharma Rao Balakrishnan; Aziz, ANA; Ismail I. (Univ Tun Hussein Onn Malaysia, 2024)
Indexed by WOS/ Scopus